Do insulin-like growth factor associated proteins qualify as a tumor marker? Results of a prospective study in 163 cancer patients - Matuschek, G (BioMed Central, 2011)
OBJECTIVE: Insulin-like growth factor (IGF)-1, -2 and Insulin like growth factor binding proteins (IGFBP) are involved in the proliferation and differentiation of cells. It has never been evaluated, if the IGF-system can serve as a tumor marker in neoplasms. METHODS: In our prospective study 163 patients with colorectal cancer (22), prostate cancer (21), head and neck tumors (17), lymphomas (20), lung cancer (34) and other entities (49) were analysed for their IGF and IGFBP serum levels at the beginning and the end of radiotherapy and compared to 13 healthy people. Subgroups of patients with local tumor disease versus metastatic disease, primary and recurrent therapy and curative versus palliative therapy were compared. RESULTS: The serum levels of IGF-2 were significantly elevated in patients with prostate and colorectal cancer. However, sensitivity and specificity were only 70%. IGFBP-2 serum levels were elevated in patients with head and neck tumors. Again sensitivity and specificity were only 73%. A difference between local disease and metastatic disease could not be found. A difference between IGF serum levels before and after radiotherapy could not be detected. CONCLUSION: The IGF-system cannot serve as a new tumor marker. The detected differences are very small, sensitivity and specificity are too low. IGF measurement is not useful for the evaluation of the success of radiotherapy in malignancies.